A avaliação social do idoso dependente na assistência domiciliar - Moreira, Marcia Pereira Santos (2005)
This research, on the social worker's professional practice, focused the dependent senior's social evaluation in home attendance, rendered by a hospitalar service. The home attendance is a modality of attention to health in which a team of professionals makes the service in the patient's own home. The senior dependent, main user of the home attendance is the person that lost his or her functional capacity in reason of worsening that happened to his or her health turning he or she partially or totally disabled. The social evaluation is a procedure used by the social worker to obtain the knowledge of the reality of the person's life in the context in that he or she lives. The literature that describes the instrumental technic of the Social Work is very restricted justifying the importance of writting more on the professional practice. The objective of this study was to identify the constituent elements of the dependent senior's social evaluation in the Program of Home Attendance of the Academical Hospital of the University of São Paulo. For so, 24 profiles of patients' attended by the Program were selected of which the Social Evaluation Record and Social Report were used. Starting from this research, it was possible to choose some aspects to be considered in the dependent senior's social evaluation in home attendance: physical, cultural, emotional and socioeconomic patient and his or her family characteristics; the composition, structures and family dynamics; the condition of the cares rendered the patient, the conditions of the home, the social support and the eligibility criteria established by for the institution